Analysis of Marketing Strategies Using SWOT Matrix and QSPM Methods - Salsabila, Fathya Hasya; Millanyani, Heppy; Sagita, Ardio (ADPEBI, 2024)
The development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia is now continuing to increase in quite significant numbers, which makes sellers have to improve their marketing strategies in facing competition, one of which is Sate Asin Pedas Bang Ote which is an MSME in Bandung City which focuses on selling spicy salted satay and experienced unstable sales because it was influenced by marketing strategies that were not optimal and consistent. This research aims to determine the internal and external environmental conditions as well as alternative marketing strategies that Sate Asin Pedas Bang Ote can implement. The research methods used are qualitative methods. Based on the SWOT analysis results, an IFE Matrix with a score of 3.322580645 and an EFE Matrix with a score of 3.526315789 was obtained, showing that the IE matrix position is in quadrant 1. Alternative marketing strategies that can be implemented are increasing sales promotions by participating in events or MSME exhibitions organized by the government or local organizers with a TAS score of 5.269949066.